Frequency of Peripheral Arterial Disease among Diabetic Patients - Nasir Ali, Samiullah, Saeed Maqsood, Tariq Ahmed, Shahzad, Rabnawaz Khan (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Peripheral artery disease, or PAD, is among the significant macro-vascular problems of diabetes mellitus and is connected with the cardio death rate and a higher rate of impairment after extremity amputation in people with diabetes. For that reason, the present research is targeted at figuring out the frequency as well as corresponding elements of Peripheral artery disease among diabetic patients at Hayatabad Medical Complex MTI, Peshawar. Place and Duration of study: Hayatabad Medical Complex MTI, Peshawar, Pakistan. The duration of the study was 6 months from 5th September 2021 to 5th March 2022. Methods: An institution based cross sectional research had been carried out among diabetes mellitus patients. A pre-tested interviewer administered a survey had been utilized to gather the information. The existence of stenosis, as well as its grading, had been influenced by color Doppler ultra-sonography. Adjusted odds ratios, along with their confidence interval (CI), were calculated for possible predictors within the ultimate model. P = 0.05 had been utilized to declare mathematical significance. Results: The mean chronological age of the research respondents was 60.5 ± 8.4 years. Two hundred fifty (55.5 %) sufferers were men, and two hundred (44.4%) were women. Sixty-seven (63.4%) sufferers were symptomatic. Age (adjusted odds ratio = 2.11 (2.45-3.11), high Glycated Hemoglobin (adjusted odds ratio = 3.87 (3.53-6.98)), as an ex-smoker (adjusted odds ratio = 5.78 (3.73-22.12), and present cigarette smoker (adjusted odds ratio = 10.12 (3.90-38.34)) were considerably connected with peripheral artery disease. Conclusion: The frequency of peripheral artery disease between people with diabetes was higher. Growing age, higher Glycated Hemoglobin, and smokers boost the probability of developing peripheral artery disease. Physicians must protect against peripheral artery disease, screen diabetic sufferers aged with higher Glycated Hemoglobin and people who smoke and treat them on time.